ANALISIS KADAR UREUM DAN KADAR GLUKOSA DARAH PUASA PADA PEROKOK KONVENSIONAL DAN PEROKOK VAPE USIA PRODUKTIF 18-21 TAHUN - Nazla Filda Apriliani (Jurnal Sains dan Teknologi Laboratorium Medik, 2023)
Conventional cigarettes and vape cigarettes contain nicotine. Nicotine in cigarettes has an influence on urea levels and blood glucose levels. The aim of this research is to determine urea levels and fasting blood glucose levels in conventional smokers and vape smokers of productive age 18-21 years. This type of research is descriptive and the variable in this research is 18-21 years old. The sampling technique uses purposive sampling technique. Samples were taken by taking venous blood which was then checked for urea levels and fasting blood glucose levels using a spectrophotometer. The data analysis used in this research is univariate analysis.The research results obtained: the average urea level of conventional smokers was 20.07 mg/dL and that of vape smokers was 20.85 mg/dL, the fasting blood glucose level of conventional smokers was 81.18 mg/dL and that of vape smokers was 77.04 mg/dL. The percentage of urea levels for conventional smokers is 93% normal, 7% is not normal, while vape smokers are 100% normal, not normal, 0%. The percentage of fasting blood glucose levels for conventional smokers is 60% normal, 40% abnormal, while for vape smokers it is 47% normal and 53% abnormal. Based on these results, both the average and percentage of urea levels and fasting blood glucose levels in conventional smokers and vape smokers of productive age 18-21 years are still within normal limits. Keywords: Conventional cigarettes, Fasting blood glucose, Urea, Vape cigarettes